5(x-4)+3x-9x=6-(2x-5)+8x

Simple and best practice solution for 5(x-4)+3x-9x=6-(2x-5)+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)+3x-9x=6-(2x-5)+8x equation:


Simplifying
5(x + -4) + 3x + -9x = 6 + -1(2x + -5) + 8x

Reorder the terms:
5(-4 + x) + 3x + -9x = 6 + -1(2x + -5) + 8x
(-4 * 5 + x * 5) + 3x + -9x = 6 + -1(2x + -5) + 8x
(-20 + 5x) + 3x + -9x = 6 + -1(2x + -5) + 8x

Combine like terms: 5x + 3x = 8x
-20 + 8x + -9x = 6 + -1(2x + -5) + 8x

Combine like terms: 8x + -9x = -1x
-20 + -1x = 6 + -1(2x + -5) + 8x

Reorder the terms:
-20 + -1x = 6 + -1(-5 + 2x) + 8x
-20 + -1x = 6 + (-5 * -1 + 2x * -1) + 8x
-20 + -1x = 6 + (5 + -2x) + 8x

Combine like terms: 6 + 5 = 11
-20 + -1x = 11 + -2x + 8x

Combine like terms: -2x + 8x = 6x
-20 + -1x = 11 + 6x

Solving
-20 + -1x = 11 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-20 + -1x + -6x = 11 + 6x + -6x

Combine like terms: -1x + -6x = -7x
-20 + -7x = 11 + 6x + -6x

Combine like terms: 6x + -6x = 0
-20 + -7x = 11 + 0
-20 + -7x = 11

Add '20' to each side of the equation.
-20 + 20 + -7x = 11 + 20

Combine like terms: -20 + 20 = 0
0 + -7x = 11 + 20
-7x = 11 + 20

Combine like terms: 11 + 20 = 31
-7x = 31

Divide each side by '-7'.
x = -4.428571429

Simplifying
x = -4.428571429

See similar equations:

| 0.6x+0.8660y-784.8=0 | | x*x-2=11 | | -5+3v=3v-5 | | 2x+7y=18 | | X-5=-54 | | 9s+12s+4=0 | | -13+5x=4x-7-2 | | 4x-17=4x+16 | | d=4.7+2.8(7.4) | | x*x-2=31 | | 6n+8=6n | | 8y+8=7y-2 | | -8x-x=-16-x | | d=4.7+2.8(12) | | 15+5m=-1+3m | | -3-6v=-v-6v | | =.8(x-25) | | 2.10+12.99b=12.39 | | -9+2k=-2k+7k | | -8a+6a=-2-4a | | 8n-4=-4+8n | | 4cosx+3sinx=y | | 5(X-15)2=75 | | 2a-4+2a=-12+3a | | n+8+2n-4=7+4n-20 | | x+2(-2)=-1 | | 8(4+7n)-6n=332 | | 6=k+7 | | 5x+5-6x=-x+5 | | y-5/y=10/8 | | m-15/4-4m-4/5=2 | | 25t^2+30x+7=0 |

Equations solver categories